O6-alkylguanine-DNA Alkyltransferases in Microbes Living on the Edge: From Stability to Applicability - Rosanna Mattossovich (International Journal of Molecular Sciences, 2020)
The genome of living cells is continuously exposed to endogenous and exogenous attacks, and this is particularly amplified at high temperatures. Alkylating agents cause DNA damage, leading to mutations and cell death; for this reason, they also play a central role in chemotherapy treatments. A class of enzymes known as AGTs (alkylguanine-DNA-alkyltransferases) protects the DNA from mutations caused by alkylating agents, in particular in the recognition and repair of alkylated guanines in O6-position. The peculiar irreversible self-alkylation reaction of these enzymes triggered numerous studies, especially on the human homologue, in order to identify effective inhibitors in the fight against cancer. In modern biotechnology, engineered variants of AGTs are developed to be used as protein tags for the attachment of chemical ligands. In the last decade, research on AGTs from (hyper)thermophilic sources proved useful as a model system to clarify numerous phenomena, also common for mesophilic enzymes. This review traces recent progress in this class of thermozymes, emphasizing their usefulness in basic research and their consequent advantages for in vivo and in vitro biotechnological applications.